Calcareous nannoplankton from Callovian deposits of Kanev’s dislocation region - Matlaj, L.M. (Reports of the National Academy of Sciences of Ukraine, 2016)
The calcareous nannoplankton in the Callovian deposits from various regions of the Kanev district is studied. The presence of coccolites with various sizes in the Early Callovian deposits testifies to the un stable salinity of a sedimentation basin. The calcareous nannoplankton is an important indicator of normal marine conditions of a sedimentation basin.